(untitled) (Stato, Chiese e pluralismo confessionale, 2022)
SOMMARIO: 1. Premessa - 2. La realtà ecclesiale e i riti - 3. La Chiesa armena gregoriana - 4. la Chiesa copta d’Egitto - 5.La Chiesa etiope e la Chiesa eritrea - 6- La Chiesa siro-giacobita - 7. La Chiesa siriaca orientale o malankarese - 8. La Chiesa assiro-orientale o caldea. The Ancient Oriental Churches and their conformity to the calcedonese faith ABSTRACT: Historical and doctrinal genesis of the non-chalcedon Churches and their current consistency. The recent clarification about the Christology of many of these Churches, especially in documents common with the Catholic Church.